Judaism and the idea of the law. Leo Strauss and Yeshayahu Leibowitz's philosophical and ideological interpretations of Maimonides - Rechnitzer, Haim O. (Hebrew Union College annual / Jewish Institute of Religion, 2008)
The ideas of the modern Jewish thinkers Leo Strauss and Yeshayahu Leibowitz share a common root. Both men place the interpretation of Maimonides at the center of their research and their own philosophical statements. Both emphasize the centrality of the Law (halakhah) as the core of Judaism and draw heavily on Maimonides to support their claims. Although Strauss and Leibowitz agree on the centrality of the Law in Maimonidean thought, they differ in interpreting the meaning of the Law in Maimonides. Strauss views the task of the Law as the creation of a political theology and identifies the Maimonidean ideal archetype as Moses, the lawgiver and leader. Leibowitz views the Law as the vehicle for the transformation of the individual and society from the realm of mundane existence into a state of true devotion to God. Leibowitz embraces Abraham as the Maimonidean archetype, seeing in him the personification of belief and an existential religious ideal. Despite their opposing interpretations of Maimonides, both reject attempts to read the liberal ideal of separation of religion and state into Judaism. Neither thinker would accept this separation as ideal for a "good society" or for the Jewish polity. Both promote this separation as a compromise position, never the ideal.